Keadilan Transisional Sebagai Upaya Penyelesaian Pelanggaran Berat Hak Asasi Manusia Di Indonesia - Woro Winandi (Darma Cendika Catholic University, 2015)
Grave violations human rights (human rights) which occurred in authoritarian countries pose victims of serious violations of human rights. As a result, during the transition from an authoritarian regime to a democratic regime came the serious human rights violations settlement demands voiced by victims of serious human rights violations and their heirs. Similar conditions also occur in Indonesia, which was once ruled by authoritarian regimes that use repressive laws to keep themselves in power in the period 1966-1998. Along reformasi in 1998, there was a period of transition in Indonesia, which brings the impact of reforms in all areas, including judicial reform.